A correlation between School Adjustment and Mathematics Achievement among Kenyan Secondary School Students - Kirui, Joash Mwandike; Dinga, Jotham; Oyoo, Syprine (Journal of Advanced Psychology, 2025)
Purpose: Mathematics is the foundation of knowledge, yet poor achievement is a concern for education stakeholders as students struggle to balance passion with performance. Methodology: This study used a correlational research design with a targeted population of all Form Three students enrolled in Kajiado County. Three hundred and ninety (390) secondary school students constituted the sample. A purposive sampling technique was used to select ten (10) schools in the County, a stratified sampling technique was used to select schools from the various categories, and simple random sampling was used to select 390 students from the ten schools. The instrument used for data collection was modified from the Student Adaptation to College Questionnaire (SACQ) (r=0.85). Additionally, the participants’ academic records provided data on their mathematics achievement. The relationship between school adjustment and mathematics achievement was tested using the Pearson’s product-moment correlation coefficient. Findings: The results showed a significant positive correlation between students’ school adjustment and mathematical achievement (r =.34, p<.05). Furthermore, this study found that academic, social, emotional, and institutional school adjustment subscales accounted for 30% of the variance in math achievement. This study concluded that school adjustment is an important individual factor that enhances students’ mathematics achievement. Unique contributions to theory, practice, and policy: This study adds to the body of knowledge by emphasizing the unique contributions of school adjustment to students' mathematical success. It provides policymakers with information by highlighting the need for customized school adjustment support programs. It provides teachers and school counselors with practical guidance for creating interventions that support healthy school adjustment and improve mathematics achievement in students from diverse backgrounds.